Microstructural And X-Ray Structural Analysis Of Nitro-Oxidized Annealed Steel (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article examines the structural and phase changes of surface diffusion nitride-oxide coatings obtained in the process of nitriding in a gas medium followed by oxidation in water vapor of ferrite-pearlite steels, as well as the effect of phase changes on corrosion properties.